Techniques Used in Estimation of Radar Range, Radar Cross Section and Moving Targets - Khulbe, Manisha (Research Highlights in Science and Technology Vol. 2, 2023)
Radar system proves to be a boon for the military based applications in detecting the enemies and identifying their locations on map. The recent advancement in the system includes applications such as air traffic control and remote sensing.The paper will provide an analysis of Radar Signal Processing to detect the range of the targets, radar cross section and direction finding. It includes that target is stationary under low noise condition and high noise conditions, radar is stationary while the target is moving under the influence of noise, interference and clutter. Another very important parameter being identified is Radar Cross Section (RCS) using approximate method for detecting the target. In this research, Signal processing methods are given for the detection of stationary and moving targets. These approximate methods are less time consuming then the exact techniques of target imaging.Various experiments have been simulated using MATLAB and simulink.